2021
DOI: 10.1097/md.0000000000026281
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous functional connectivity within the default-mode network in treatment-naive patients possessing first-episode major depressive disorder

Abstract: Background and Objective: Previous studies have shown that the default-mode network (DMN) has a substantial role in patients with major depressive disorder (MDD). However, there is a shortage of information regarding variations in the functional connectivity (FC) of the DMN of treatment-naive patients with first-episode MDD. The present study aims to explore the FC of the DMN in such patients. Methods: The study population consisted of 33 patients and 35 controls, paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Major depressive disorder (MDD) is a common psychiatric condition and leads to significant physical, psychological, and economic distress in individuals, families, and society[ 1 , 2 ]. Traumatic experiences during childhood, as shown by a meta-analysis[ 3 ], are significant psychosocial risk factors for MDD, and their presence represents a major reason for the refractory and recurrent nature of depression[ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is a common psychiatric condition and leads to significant physical, psychological, and economic distress in individuals, families, and society[ 1 , 2 ]. Traumatic experiences during childhood, as shown by a meta-analysis[ 3 ], are significant psychosocial risk factors for MDD, and their presence represents a major reason for the refractory and recurrent nature of depression[ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the pathogenesis of MDD remains unclear, with its clinical diagnosis being mainly based on symptoms ( Gao et al, 2019 ; Yu et al, 2021 ). At the same time, due to self-reports and doctor bias, misdiagnosis and missed diagnosis may also occur.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported abnormal FC with inconsistent results in patients with MDD. For instance, patients with MDD in one study showed decreased FC between the medial orbitofrontal gyrus ( Yu et al, 2021 ) and cerebellum ( Zhu et al, 2020 ), whereas patients in another work exhibited increased homotopic FC ( Liu et al, 2020 ) in the same brain regions.…”
Section: Introductionmentioning
confidence: 99%